Enhancing the Anticancer Activity of Antrodia cinnamomea in Hepatocellular Carcinoma Cells via Cocultivation With Ginger: The Impact on Cancer Cell Survival Pathways - Chen, San-Yuan; Lee, Ying-Ray; Hsieh, Ming-Chia; Omar, Hany A.; Teng, Yen-Ni; Lin, Ching-Yen; Hung, Jui-Hsiang (Frontiers in Pharmacology, 2018)
Antrodia cinnamomea (AC) is a medicinal fungal species that has been widely used traditionally in Taiwan for the treatment of diverse health-related conditions including cancer. It possesses potent anti-inflammatory and antioxidant properties in addition to its ability to promote cancer cell death in several human tumors. Our aim was to improve the anticancer activity of AC in hepatocellular carcinoma (HCC) through its cocultivation with ginger aiming at tuning the active ingredients. HCC cell lines, Huh-7 and HepG2 were used to study the in vitro anticancer activity of the ethanolic extracts of AC (EAC) alone or after the cocultivation in presence of ginger (EACG). The results indicated that the cocultivation of A. cinnamomea with ginger significantly induced the production of important triterpenoids and EACG was significantly more potent than EAC in targeting HCC cell lines. EACG effectively inhibited cancer cells growth via the induction of cell cycle arrest at G2/M phase and induction of apoptosis in Huh-7 and HepG2 cells as indicated by MTT assay, cell cycle analysis, Annexin V assay, and the activation of caspase-3. In addition, EACG modulated cyclin proteins expression and mitogen-activated protein kinase (MAPK) signaling pathways in favor of the inhibition of cancer cell survival. Taken together, the current study highlights an evidence that EACG is superior to EAC in targeting cancer cell survival and inducing apoptotic cell death in HCC. These findings support that EACG formula can serve as a potential candidate for HCC adjuvant therapy.